The power of real language: The importance of authentic texts (newspaper articles) in teaching reading competence - Turg’unboyev Muhammadbobur Faxriddin o’g’li (Periodica Journal, 2025)
This article discusses the importance of newspaper articles as authentic texts in teaching reading skill. In this article, the concept of reading and reading comprehension are defined, with explaining how to teach it to students using newspaper articles. Form 10 students are chosen as a sample population of this study and most students are inclined to boost their reading comprehension through getting exposed to newspaper articles easily and efficiently. The result of this study is expected to help teachers to teach reading skill using new teaching strategies which encourage their students to learn more and enhance their reading comprehension
Keywords: authentic texts; newspaper articles; reading comprehension and reading competence